Is There a Mild Form of Pediatric Appendicitis? An Eight-Year Single-Center Retrospective Review - Eric Scheier; Khaled Khalilia; Pavel Peslin; Stav Amir; Luba Pasherstnik Bizer (Emergency Care and Medicine)
Introduction: The literature has suggested two variants of appendicitis: a simple variant that may even resolve spontaneously and a more aggressive variant that may proceed to complication. We review two cohorts compatible with “mild” appendicitis: children with acute appendicitis that presented with normal inflammatory markers (NIMs), and confirmed on pathological examination, and children with sonographically confirmed appendicitis that resolved without medical or surgical intervention. Methods: We identified all children diagnosed with appendicitis from June 2016 to June 2024. To confirm the accuracy of the initial sonographic diagnosis of appendicitis in children with spontaneous resolution, two study radiologists, blinded to clinical data, reviewed the images for signs of appendiceal inflammation. We compared cases of NIM with cases presenting with elevated inflammatory markers, and cases of spontaneous resolution with cases of uncomplicated appendicitis treated medically. Results: A total of 999 children were diagnosed with appendicitis, with 845 confirmed on pathology. Of these 845, 17 had NIMs and were less likely to present with vomiting than children with elevated inflammatory markers (24% versus 61%, p = 0.002). Fourteen had spontaneous resolution and twenty-five were treated medically. White blood cell count (14.1 versus 10.2, p = 0.005) and appendiceal diameter (8.6 mm versus 7.6 mm, p = 0.078) were higher for children with conservative treatment. Children receiving medical treatment received intravenous analgesia more frequently (88% versus 50%, p = 0.009). More resources were used for medical treatment—these children had longer hospitalizations (3.5 versus 1.6 days, p = 0.001) and more frequently received repeat bloodwork (68% versus 36%, p = 0.051). Conclusions: Appendicitis that resolves spontaneously, and appendicitis that presents with normal inflammatory markers, may represent rare, low-risk forms of appendicitis that may not be associated with progression to complication. While pediatric appendicitis should not be ruled out in the presence of a normal laboratory evaluation, cases that present without gastrointestinal symptoms, without severe pain, and with an appendiceal diameter and inflammatory markers below a certain threshold may warrant continued observation and serial ultrasound to evaluate for progression prior to initiating therapy.